MORPHOMETRIC CHARACTERISTICS OF RED SOKOTO GOATS IN SOME SELECTED LOCAL GOVERNMENT AREAS OF BAUCHI STATE, NIGERIA - Haruna, H. M.; Kalla, D. J. U.; Mai, H. M.; Magaji, I. M. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study was conducted to determine the morphometric characteristics of Red Sokoto Goats (RSG) in Dambam, Gamawa and Misau Local Government Areas of Bauchi State. A total of six hundred (600) RSG were used for the study, out of which 121 were males and 479 were females. Body condition score (BCS) was assessed subjectively through principally massaging the loin region, abdominal fat and chest cavity and scored using the 5 points scale (where; 1 = very thin, 2 = thin, 3 = average, 4 = fat and 5 = Very fat/ obese) for both sexes. The effects of location and sex on morphometric characteristics were also determined. The qualitative traits recorded via visual observation included: coat colour, presence or absence of beard, wattle and supernumerary teat. Morphometric traits measured using tailor’s tape and recorded in cm were: head length, ear length, horn length, chest girth, height at wither, body length, loin girth, rump length, rump height, rump width, tail length, udder length, udder circumference, teat length, scrotal circumference and scrotal length. The live body weight was measured using a digital weighing scale in kg. However, the study revealed that the RSG found in Gamawa had the highest values for all the significantly different parameters, while the least values were recorded on RSG in Misau (38.26±0.41 vs 24.16±0.41). Sex is confirmed to have influence on live weight (P < 0.05) where the male appeared to be heavier than the female animals. The effects of qualitative traits on morphometric characteristics were determined and found out that they have little to less impact on growth parameters.